Gabon health care system: a 20 year analysis - Obiang Obounou, Brice Wilfried (International Journal Of Community Medicine And Public Health, 2017)
In response to a high prevalence of HIV/AIDS and malaria, the government of Gabon launched the National Insurance and Social Welfare Fund in 2008. It is a national health insurance fund voted by the parliament to extend health-care coverage to the country’s different socioeconomic groups, bringing everyone under one social health insurance roof. Analysis of the WHO, World Bank and available data from 1995 to 2014 to evaluate progress before and after the creation of the universal health coverage. Maternal health is fully covered and the cost of medical care is reimbursed by 80-90%. However, out-of-pocket spending (21.87%) as a percentage of total health care spending is still higher that other Sub-Saharan African countries classified in the upper-middle income countries. The government and policy makers should increase health care system financing and work in partnership with private clinics regarding over-servicing and over billing.